The Chankas and the Priest : A Tale of Murder and Exile in Highland Peru - Hyland, Sabine, 1964- (Book collections on Project MUSE., 2016)
"Presents the story of the Chanka people of Peru, from the fifteenth to the eighteenth centuries, told through a narrative of the crimes committed by a priest, Juan Bautista de Albadán, in the early 1600s"--Provided by publisher